PEMERIKSAAN HEMOGLOBIN DAN HEMATOKRIT DALAM RANGKA DETEKSI DINI ANEMIA PADA PEREMPUAN USIA SUBUR DI JAKARTA UTARA - Wijaya, Christian; Santoso, Alexander Halim; Destra, Edwin; Sukianto, Louise Audrey; Ismi, Arni (BAMALA Institute, 2025)
Anemia among women of childbearing age remains a significant public health concern in Indonesia, directly affecting both quality of life and maternal health outcomes. Early detection through hemoglobin and hematocrit testing plays a critical role in preventing complications and improving health status. This community service activity was conducted using the Plan–Do–Check–Act (PDCA) framework to enhance awareness among women of reproductive age regarding anemia, its risk factors, and preventive strategies. Educational sessions were delivered through counseling, followed by hemoglobin and hematocrit examinations. The average hemoglobin level among participants was 11.44 g/dL and hematocrit was 33.76%, both below the normal thresholds, indicating a potential risk for anemia. Participants reported improved understanding of the importance of maintaining a nutritious diet and undergoing routine health check-ups. The intervention demonstrated that education combined with early screening through hemoglobin and hematocrit assessments can effectively reduce the risk of anemia in women of reproductive age. This program supports increased health literacy and contributes to anemia prevention efforts in this vulnerable population. Keywords: Anemia, Early Detection, Hematocrit, Hemoglobin, Women Of Childbearing Age